La production des enquêtes quantitatives - Rémy Caveng (Revue d'anthropologie des connaissances)
In texts about quality of quantitative surveys and in selling point of surveys institutes, reference is made to the necessary standardization of data collection and to the reduction of the “interviewer effect”. To achieve this ideal, should be applied a set of rules. But the fieldwork’s reality is very far of this standard and the interviewers change the protocol. Several reasons for this: the completion of a questionnaire, like any social interaction, can’t be totally standard; the expected level of productivity is not compatible with the quality rules; the working conditions, the employment relations and the level of remuneration disincentive to follow rules. A realistic and pragmatic definition of data quality implies taking into account these three dimensions.